Pemberdayaan UMKM Melalui Pemanfaatan Teknologi Informasi - Muhammad Eko Atmojo (Universitas Lancang Kuning, 2022)
This service was carried out in Gilangharjo Village, Pandak District, Bantul Regency, where the focus of community service was assistance to the MSME sector in the use of information technology. Given that, Gilangharjo Village is a village center for MSME, during the Covid-19 pandemic; the MSME sector was seriously affected. One way to keep the MSME sector hopeful during a pandemic is to take advantage of information technology. The methods used in the implementation of the service include observation, socialization, and training on creating social media accounts. Whereas the result of the implementation of this service is the formation of awareness of MSME players of the benefits of information technology, besides the importance of the existence of MSMEs to increase Indonesia's economic growth. In addition, the results of this dedication also resulted in an increase and understanding of MSME players in using information technology, especially social media as a marketplace in selling MSME products.